Introduction to water quality modelling - Vishnuradhan, Renjith; Zaki, Zainudin, Ir. Assoc. Prof. Dr.; Vethamony, P., Prof. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.my/